2017
DOI: 10.29090/psa.2017.03.142
|View full text |Cite
|
Sign up to set email alerts
|

Detection of adverse drug reaction (ADR)-related hospital admissions: A pilot study using administrative database for ADR monitoring in Thailand

Abstract: This study aims to examine incidence, characteristics, and trend of ADR-related admissions at one tertiary care hospital in Thailand during a five-year period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the characteristics of ADEs in our study differed from those in other countries. For example, in a retrospective study examining ADR-related hospital admissions at a single hospital in Thailand, ‘drug-induced neutropenia’ was the most common ( Siltharm et al, 2017 ). Another study conducted in England, Germany, and the United States revealed that ‘Enterocolitis due to Clostridium difficile ’ was the most frequent type of ADEs ( Stausberg, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the characteristics of ADEs in our study differed from those in other countries. For example, in a retrospective study examining ADR-related hospital admissions at a single hospital in Thailand, ‘drug-induced neutropenia’ was the most common ( Siltharm et al, 2017 ). Another study conducted in England, Germany, and the United States revealed that ‘Enterocolitis due to Clostridium difficile ’ was the most frequent type of ADEs ( Stausberg, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…From earlier reviews [17,[23][24][25]27,28], findings have reported the presence of methodological heterogeneity between studies measuring ADR costs in terms of assessing causal relationships between the drug and the resulting morbidity, and how to define ADR. This is similar to our review, where there is also a large heterogeneity between the methods and cost sources used for cost analysis within these studies.…”
Section: Streamlining Adr Costing Methodsmentioning
confidence: 99%
“…However, the current scarcity of evidence, on top of the heterogeneity of findings, makes the interpretation of findings difficult. For instance, between 1998 and 2013, there were at least 14 systematic reviews on the incidence and risk factors of ADRs [6,[17][18][19][20][21][22][23][24][25][26][27][28]. Out of this, only three of them [17,25,27] looked into ADR costs while only one [29] explored the potential effect of methodological approaches to cost estimations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation